2020
DOI: 10.1074/jbc.ra120.013537
|View full text |Cite
|
Sign up to set email alerts
|

Bioenergetic defects in muscle fibers of RYR1 mutant knock-in mice associated with malignant hyperthermia

Abstract: Mutations in the skeletal muscle ryanodine receptor gene (RYR1) can cause susceptibility to malignant hyperthermia (MH), a potentially lethal genetic condition triggered by volatile anesthetics. MH is associated with hypermetabolism which has directed research interest into oxidative phosphorylation (OXPHOS) and muscle bioenergetics. The most common cause of MH in the United Kingdom is the c.7300G>A RYR1 variant, which is present in ~16% of MH families. Our study focuses on the MH susceptible G2435R-RYR1 kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…Laboratory studies on the effects of aging and altered calcium metabolism on late-onset muscle weakness in mice have shown that the higher resting cytosolic calcium concentrations, as observed in skeletal muscle cells of MH susceptible individuals, 41 , 42 may cause myofibrillar disarray, sarcolemmal rupture, structural alterations such as cores and, mitochondrial damage. 43 , 44 Interestingly, the RYR1 knock-in mouse model used in one of these studies (p.Gly2435Arg) corresponds with the human RYR1 c.7300G > A, p.Gly2434Arg variant, 44 which was also found in one of the patients with late-onset proximal muscle weakness identified in our study. Furthermore, structural alterations in skeletal muscle cells of MH susceptible mice appear to increase in severity with age.…”
Section: Discussionsupporting
confidence: 70%
“…Laboratory studies on the effects of aging and altered calcium metabolism on late-onset muscle weakness in mice have shown that the higher resting cytosolic calcium concentrations, as observed in skeletal muscle cells of MH susceptible individuals, 41 , 42 may cause myofibrillar disarray, sarcolemmal rupture, structural alterations such as cores and, mitochondrial damage. 43 , 44 Interestingly, the RYR1 knock-in mouse model used in one of these studies (p.Gly2435Arg) corresponds with the human RYR1 c.7300G > A, p.Gly2434Arg variant, 44 which was also found in one of the patients with late-onset proximal muscle weakness identified in our study. Furthermore, structural alterations in skeletal muscle cells of MH susceptible mice appear to increase in severity with age.…”
Section: Discussionsupporting
confidence: 70%
“…It has been hypothesized that the mitochondrial dysfunction observed in MHS muscle may be a consequence of the elevated intracellular [Ca 2+ ] and increased oxidative stress associated with RYR1 variants. Increased oxidative stress and the accumulation of reactive oxygen species (ROS) have been consistently reported in the muscle of various MH mouse models [ 10 , 13 , 14 , 27 ]. The interplay between ROS and Ca 2+ has an important role in regulating cellular metabolism and its dysregulation has detrimental effects on mitochondria [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The biological consequences of specific RYR1 variants have been investigated using different knock-in mouse models [ 6 , 7 , 8 , 9 ]. Mitochondrial dysfunction has been a consistent feature in MH-associated RYR1-knock in mouse models and has been speculated to be a potential influencer of the MH muscle phenotype [ 7 , 10 , 11 , 12 , 13 , 14 ]. Although limited, this parallels data from studies of human MHS muscle that have shown evidence of mitochondrial structure abnormality using electron microscopy [ 15 ], and functional deficits detected through high-resolution respirometry [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is, initially, translated into activation of a preserving mechanism that leads to increased ATP production to support the greater demand of ATP exerted by SERCA pumps in their continuous activity to counteract Ca 2+ leak ( Lamboley et al, 2021 ). Nevertheless, in the long term, mitochondria from both Ryr1 G2434R/WT and Ryr1 T4826I/WT mice showed structural and functional alterations, mainly in fatty acid metabolisms, that resulted in lipotoxicity and an increase in oxidative stress, impacting muscle bioenergetics and muscle performance ( Yuen et al, 2012 ; Chang et al, 2020 ). Similarly, muscles from Ryr1 R163C/WT mice show an increase in excitation contraction calcium entry (ECCE) linked to delayed inactivation of L-type currents through DHPR ( Cherednichenko et al, 2008 ; Bannister et al, 2010 ; Estève et al, 2010 ); both Ryr1 R163C/WT and Ryr1 Y522S/WT also display an increase in SOCE that may contribute to Ca 2+ overload, hypercontractures, heat generation, and rhabdomyolysis ( Eltit et al, 2013 ; Yarotskyy et al, 2013 ).…”
Section: Gain-of-function Mutations In Ryr1: In Vitro Characterizatio...mentioning
confidence: 99%